1997
DOI: 10.1074/jbc.272.43.26965
|View full text |Cite
|
Sign up to set email alerts
|

Dantrolene Inhibition of Sarcoplasmic Reticulum Ca2+Release by Direct and Specific Action at Skeletal Muscle Ryanodine Receptors

Abstract: The skeletal muscle relaxant dantrolene inhibits the release of Ca 2؉ from the sarcoplasmic reticulum during excitation-contraction coupling and suppresses the uncontrolled Ca 2؉ release that underlies the skeletal muscle pharmacogenetic disorder malignant hyperthermia; however, the molecular mechanism by which dantrolene selectively affects skeletal muscle Ca 2؉ regulation remains to be defined. Here we provide evidence of a high-affinity, monophasic inhibition by dantrolene of ryanodine receptor Ca 2؉ channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
169
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 43 publications
21
169
0
2
Order By: Relevance
“…In agreement with previous reports (7,12,13,45,46), we found that the extent of dantrolene inhibition of DP4-induced RyR1 channel activation, as determined by both [ 3 H]ryanodine binding and SR Ca 2ϩ release, varies with the temperature, i.e. significant inhibition was observed at 37°C, with only negligible inhibition at 22°C.…”
Section: Table III Inhibition Of Sr Ca 2ϩ Release By Dantrolene: Effesupporting
confidence: 81%
See 3 more Smart Citations
“…In agreement with previous reports (7,12,13,45,46), we found that the extent of dantrolene inhibition of DP4-induced RyR1 channel activation, as determined by both [ 3 H]ryanodine binding and SR Ca 2ϩ release, varies with the temperature, i.e. significant inhibition was observed at 37°C, with only negligible inhibition at 22°C.…”
Section: Table III Inhibition Of Sr Ca 2ϩ Release By Dantrolene: Effesupporting
confidence: 81%
“…CaM alone (1 M) increased the specific activity of [ 3 H]ryanodine binding to the SR at 22°C, but dantrolene was now able to significantly suppress radioligand binding (ϳ35%) (Table II). When we carried out the same type of experiments at 37°C, dantrolene produced equivalently significant inhibition of [ 3 H]ryanodine binding (ϳ59%) in the presence or absence of CaM, in agreement with previous reports (7,12,13,45). These results suggest that higher temperature and CaM have similar effects on the extent of dantrolene inhibition of DP4-induced activation of RyR Ca 2ϩ channels.…”
Section: Inhibition Of Skeletal Muscle Sr Ryanodine Binding and Ca 2ϩsupporting
confidence: 81%
See 2 more Smart Citations
“…6 Dantrolene relaxes striated muscles by inhibiting the release of Ca 2 þ from the sarcoplasmic reticulum. 7 The drug commonly causes transient drowsiness, weakness, general malaise, fatigue, diarrhea, and liver test dysfunction that requires strict laboratory follow-up. 8 The potential liver toxicity discourages some physicians from using Dantrolene, but still many use it for long periods.…”
Section: Introductionmentioning
confidence: 99%